Ultrassonografia pulmonar na identificação da dispneia aguda cardiogênica em pacientes hospitalizados - Araujo, Caroline de Souza Costa (2016)
Acute dyspnea (AD) is a common complaint in a hospital unit and frequently, differential diagnosis is a challenge despite acquirement of diverse methodologies. Lung ultrasonography (LU) has shown useful identifying AD of cardiogenic origin. However, there is a shortage of national studies confirming such quality. Objectives: Evaluate LU’s contribution on identification of cardiogenic origin AD. Methodology: This is a prospective, longitudinal cohort of patients in emergency room and admitted into hospital unit, with AD complaint. They were evaluated by Framingham risk score (FRS) for cardiac insufficiency (CI) and subjected to the following additional tests: electrocardiogram (ECG), chest radiography (CR), transthoracic ecodoppler cardiogram (TTE) and LU. Excluded pulmonary fibrosis and lung neoplasm patients. Calculated: sensitivity, specificity, positive and negative predictive value, as well as ROC curve of LU for AD diagnosis. Interobserver agreement among methods was estimated by kappa statistic. Results: From February to October of 2015, 118 patients (9 excluded) were classified according to presence or absence of CI by FRS. Of 109 cases, 60 (55%) had CI. These were elder (average age 76±16.7, p=0.01), men (60%, p=0.004), hypertensive (83%, p=0.01), diabetic (50.8%, p=0.03), with chronic renal insufficiency (CRI) (32.2%, p=0.03) and with higher adapted Killip classification (p=0.00) and functional class (p=0.003). Presented more pulmonary interstitial edema(IPE) on LU, CI to CR criteria (p=0.009) and, on TTE, higher E/e’ ratio (p=0.002) and left ventricle diastolic dysfunction (p=0.04), besides lower ejection fraction (p=0.00). Importants predictors on IPE detection by US in these patients were male gender, diabetics and with ejection fraction of reduced(p=0.01; 0.02 and 0.03, respectively). There was modest kappa agreement (k) between LU with FRS (k=0.25) and CR (k=0.22) for CI and moderate between LU (k=0,48) and CR and interobserver CR (kappa=0,44) LU sensibility for IEP in patients with CI was 90.91%, 65% specificity, 85.1% positive predictive value and 76.4% negative. Conclusion: therefore, concludes that LU proved to be a useful tool and with reproducibility when identifying AD of cardiogenic.